The pilgrim's regress : an allegorical apology for Christianity, reason, and romanticism - Lewis, C. S. (Clive Staples), 1898-1963 (William B. Eerdmans Publishing Company, 2014)
The Pilgrim's regress is, in a sense, a record of Lewis's own search for meaning and spiritual satisfaction that eventually led him to Christianity. It is the story of John and his odyssey to an enchanting island that has created in him an intense longing, a mysterious, sweet desire. John's pursuit of this desire takes him through adventures with such people as Mr. Enlightenment, Media halfways, Mr. Mammon, Mother Kirk, Mr. Sensible, and Mr. Humanist and through such cities as Thrill and eschropolis, as well as the Valley of Humiliation. Though the dragons and giants here are different from those in Bunyan's The Pilgrim's progress, Lewis's allegory performs the same function of enabling the author to say in fable form what would otherwise have demanded a full-length philosophy of religion.